2017
DOI: 10.21873/invivo.11046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caspase 9 Gene Polymorphism in Patients with Prostate Cancer

Abstract: Patient (n=69) and control (n=76) groups were selected during clinical examination at Yeditepe University, Urology Department, Turkey. Radiologic and pathological analysis performed in all patients for evaluating pathological and clinical information. After obtaining informed consent, and peripheral blood samples collected by EDTA containing tubes. Demographic characteristics (age, body mass index, serum PSA levels, smoking habitus, Gleason Scores, family histories, 205

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Yılmaz et al identified an association between the CASP-9 (rs1052576) TT genotype and stage in prostate cancer. 13 Our study results revealed that caspase-9 was numerically lower in poorlydifferentiated tumors (25.49±17.42) than moderate and well-differentiated ones (41.30±39.39); however, the difference was not statistically significant. Shen et al investigated caspase-9 levels using RT-PCR in patients with stage II colon cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…Yılmaz et al identified an association between the CASP-9 (rs1052576) TT genotype and stage in prostate cancer. 13 Our study results revealed that caspase-9 was numerically lower in poorlydifferentiated tumors (25.49±17.42) than moderate and well-differentiated ones (41.30±39.39); however, the difference was not statistically significant. Shen et al investigated caspase-9 levels using RT-PCR in patients with stage II colon cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…On the other hand, miR-133a-3p regulates genes such as EGFR, CASP9, and IGF1R (Tao et al, 2012;Pashaei et al, 2017). These genes have already been reported to be implicated in different processes of PCa, such as apoptosis, metastasis, and androgen-independence (Wu and Yu, 2014;Day et al, 2017;Yilmaz et al, 2017). miR-148b-3p ha, so far,s not been studied in depth in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…MS/MS results, re-analyzed using CMPD including largescale coding variants for cancer, have provided a collection of mutant protein sequences that correspond to large-scale (52,53). Although the details regarding the increased preference of the six mutation sites in DU145…”
Section: Discussionmentioning
confidence: 99%